Regency Clusterization Based on Village Characteristics to Increase the Human Development Index (IPM) in Papua Province - Rais; Amir Abduljabbar Dalimunthe; Anwar Fitrianto; Bagus Sartono; Sachnaz Desta Oktarina (Jurnal Ekonomi Pembangunan, 2022)
Inequality in the Human Development Index (IPM) in Papua Province amid the disbursement of development funds needs to be studied adequately so that the policies and programs that have been planned can be more directed and on target. For this reason, research is needed that can map the priority needs of each district in Papua Province by identifying regional characteristics, namely villages. By using Cluster Analysis and Factor Analysis, the results of this research show that 4 district clusters in Papua Province were formed with different priority focuses on increasing the HDI. The main focus of the district HDI improvement priorities in Papua Province is divided into three through factor analysis: the infrastructure-telecommunication factor, the sanitation-economic factor, and the health-education factor. Each cluster is generally still dominated by districts with a low HDI category. The main obstacle to increasing HDI in Papua Province is the transportation and telecommunications infrastructure factor. Local governments are expected to be able to formulate human development programs and policies concerning the priority needs of each district as a result of this research.